Air quality management in the United States - National Research Council (U.S.). Committee on Air Quality Management in the United States (Washington, D.C. : National Academies Press, 2004)
The implementation of air quality regulations should be less bureaucratic -- with more emphasis on results than process -- and should be designed to protect ecosystems as well as people. The report recommends that The Environmental Protection Agency (EPA) use an approach to target groups of pollutants instead of individual ones and that revised or new regulations also should consider how air pollution travels from state to state and across international borders. In addition, improved tracking of emissions is needed to accurately assess what populations are at the highest risk of health problems from pollution and to better measure the progress of pollution-control strategies.
""Appendix A Committee Biosketches""""Appendix B Statement of Task""; ""Appendix C 188 Hazardous Air Pollutants (HAPs)""; ""Appendix D Recommendations for Continuous Development and Implementation of Measurements to Determine Status and Trends in Ecosystem Exposure and Condition""; ""Index""
Includes bibliographical references (pages 317-348) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Air quality management -- United States; Air -- Qualité -- Gestion -- États-Unis.; TECHNOLOGY & ENGINEERING -- Environmental -- Pollution Control; Air quality management; United States; AIR QUALITY; POLLUTION CONTROL; AIR POLLUTION; MANAGEMENT; UNITED STATES; Samfundsvidenskab -- Sociologi; Electronic book